King Lear: A Negatively Capable Outsider - Hossein Salimian Rizi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
Negative capability, John Keats’s coined term, defines the ideal poet as being capable of being in uncertainties and mysteries without any irritable reaching after fact and reason. He insists that poets let the mind be a thoroughfare for all thoughts, by holding no fixed identity but metamorphic identities. Although Keats finds the ideal quality of a poet in Shakespeare the poet, it does not appear far from logical to investigate it in the characters of his plays, specifically king Lear, as he undergoes changes throughout the story and cuts across his enclosed self to enrich his receptivity to the actual vastness of life experience after he is estranged and labelled as an outsider in his erstwhile kingdom. In the present study I will employ the ongoing vigor of negative capability to take a step further ahead of its theoretically stipulated implications and investigate it on the character of king Lear.